Pitfalls of Participatory Approaches - Czyżewski, Marek (Participatory Social Work: Research, Practice, Education, 2019)
Over recent decades, “participation” has become one of the leading mottos of reform-oriented movements in such diverse fields as democracy, technology, finance, management, mass media, culture, social research methodology and, last but not least, social work. Before our eyes the “change of function” (in the terminology of Karl Mannheim) has taken place: what in the sixties and seventies was an incorporation of subversive and alternative tendencies, has been absorbed step by step in mainstream discourses on politics, economy, social science and the helping professions. The discursive dominance of participatory ideas can be manifested when they constitute a prominent message in recent handbooks in the fields mentioned above or provide apparently self-evident justifications in typical applied research projects. This trend needs to be reflected upon if we are not to succumb to the self-destructive potential of participatory approaches.